2008
DOI: 10.1166/jnn.2008.500
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sulphur in the Synthesis of Carbon Nanotubes by Chemical Vapour Deposition at High Temperatures

Abstract: Sulphur has been recognised as a growth promoter for carbon fibres and carbon nanotubes for over 30 years. Moreover, the Fe-C-S system, in particular, has been extensively studied for more than half a century in the fields of steelmaking and cast iron. In the present work we examine the role of sulphur in the iron-catalysed growth of carbon nanotubes during the process of direct spinning of fibres from the gas phase. A detailed microstructural characterisation of the reaction products was conducted by high res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 28 publications
7
60
0
Order By: Relevance
“…In this growth method, the CNT growth occurs at a higher temperature than by the other methods for the preparation of DWNTs, such as the CCVD method. By the annealing of molecules encapsulated with the SWNT, it is widely accepted that the arc discharge-produced CNTs exhibit high crystallinity and low defect density [21,[73][74][75][76][77][78][79][80][81][82][83]. While arc discharge-produced DWNTs exhibit a high oxidation temperature close to 800 • C, the defect healing at high temperature was proposed as a justification for the high quality product outcomes [73,74].…”
Section: The Arc Discharge Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this growth method, the CNT growth occurs at a higher temperature than by the other methods for the preparation of DWNTs, such as the CCVD method. By the annealing of molecules encapsulated with the SWNT, it is widely accepted that the arc discharge-produced CNTs exhibit high crystallinity and low defect density [21,[73][74][75][76][77][78][79][80][81][82][83]. While arc discharge-produced DWNTs exhibit a high oxidation temperature close to 800 • C, the defect healing at high temperature was proposed as a justification for the high quality product outcomes [73,74].…”
Section: The Arc Discharge Methodsmentioning
confidence: 99%
“…Sulfur has been used as a promoter for the growth of carbon fibers (CF) [78,79]. By introducing sulfur as a promoter, Hutchison et al [80] reported for the first time the selective growth of DWNTs, using the arc discharge method.…”
Section: The Arc Discharge Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent successes for structure prediction include a combination of theory and experiment to characterize gold clusters [61]. Systematic global optimization studies such as this are likely to play an increasing role in future work, especially for the added complexities associated with bimetallic clusters [62][63][64] (nanoalloys) and the use of non-metal additives, such as sulphur, which is known to enhance the yield and purity of carbon nanotubes grown by chemical vapour deposition using iron nanoparticles as a catalyst [65]. As a first step, an investigation of the PES of clusters bound by the FS potential using basin-hopping is required.…”
Section: Global Optimization Of Metal Clustersmentioning
confidence: 99%
“…Thermal decomposition of the iron and sulfur source leads to the nucleation of catalyst nanoparticles which act as a catalytic surface for CNT growth once sufficient carbon is available from the decomposition of the reactants. The role of sulfur is still under investigation but current research suggests it conditions the iron nanoparticles by affecting the carbon diffusivity at the surface and stimulating CNT growth [10,11]. As CNTs begin to grow, they preferentially bundle due to Van der Waals forces and these bundles intertwine to form an aerogel.…”
Section: Introductionmentioning
confidence: 99%